Financing Infrastructure under Budget Constraint - Axel Gautier; Manipushpak Mitra (University of Bonn, Bonn Graduate School of Economics (BGSE), 2002)
In this paper we consider the problem of financing infrastructure when the regulator faces a budget constraint. The optimal budget-constrained mechanism satisfies four properties. The first property is bunching at the top, that is the more efficient firms produce the same quantity. The second property is self-selection for the less efficient firms. The third property is that the mechanism is a third best one. In other words, as long as the budget-constraint is binding, the optimal output is strictly lower than the second best output for any given type. Finally, if the budget constraint is too strong, then we have a full bunching solution.
Keywords: H42; D82; L51; 330; Regulation; Asymmetric Information; Budget Constraint; Infrastrukturinvestition; Haushaltskonsolidierung; Asymmetrische Information; Budgetrestriktion; Theorie